2017
DOI: 10.1111/jerd.12316
|View full text |Cite
|
Sign up to set email alerts
|

A novel technique for reference point generation to aid in intraoral scan alignment

Abstract: Composite resin dots on keratinized tissue were successful at allowing accurate merging of provisional restoration and post-preparation 3D models for the purpose of using the provisional restorations as a guide for final CLINICAL SIGNIFICANCE: Composite resin dots placed temporarily on attached tissue were successful at allowing accurate merging of the provisional restoration 3D models to the preparation 3D models for the purposes of using the provisional restorations as a guide for final restoration design an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Gherlone related good clinical results when constructing all‐on‐4 CAFIPS trough an intraoral scanning workflow, and such results agree with the present case report as a passive fit was also noticed in the presented patient by clinical and radiographic analysis (Figure ). From the previous background, we can infer that the fabrication of a CAFIPs from intraoral scans is challenging as the recording of hard tissue reference points in complete‐arch cases is still not optimized in current intraoral scanners software and hardware …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gherlone related good clinical results when constructing all‐on‐4 CAFIPS trough an intraoral scanning workflow, and such results agree with the present case report as a passive fit was also noticed in the presented patient by clinical and radiographic analysis (Figure ). From the previous background, we can infer that the fabrication of a CAFIPs from intraoral scans is challenging as the recording of hard tissue reference points in complete‐arch cases is still not optimized in current intraoral scanners software and hardware …”
Section: Discussionmentioning
confidence: 99%
“…From the previous background, we can infer that the fabrication of a CAFIPs from intraoral scans is challenging as the recording of hard tissue reference points in complete-arch cases is still not optimized in current intraoral scanners software and hardware. 11,12 Some limitations can be associated with the presented workflow, as it did not include an interim prosthesis to check the esthetic and functional outcomes. This was only possible because the previous prosthesis presented a good overall result and was considered a trustworthy reference to be replicated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical data regarding the accuracy of the intraoral scanners (IOS) of edentulous arches are scarce 12,13 . Previous authors have reported different techniques to facilitate intraoral digital scans of completely edentulous arches using pressure indicating paste 14 or composite resin markers adhered to keratinized oral mucosa 14–17 . However, the composite resin markers have not been used as radiopaque references for alignment purposes of patient's digital information during static computer‐aided implant planning procedures.…”
mentioning
confidence: 99%